PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP KOMITMEN KARYAWAN PADA PT SIKARS PETROLEUM NUSANTARA TAPOS DEPOK - Muhlis; Thomas Yoshua (Institut Teknologi dan Bisnis Dewantara, 2026)
This study aims to determine the effect of compensation and job satisfaction on employee commitment at PT. Sikars Petroleum Nusantara Tapos Depok, both partially and simultaneously. This causal quantitative research was conducted from October 2024 to March 2025 with a population of 55 employees, all of whom were taken as samples using the census technique. Data analysis was performed using multiple linear regression. The results show that: (1) Compensation has a significant effect on employee commitment (t-value 4.568 > 2.004; sig. 0.000 < 0.05). (2) Job satisfaction has a significant effect on employee commitment (t-value 4.392 > 2.004; sig. 0.000 < 0.05). (3) Simultaneously, compensation and job satisfaction significantly affect employee commitment (F- value 26.872 > 2.772; sig. 0.000 < 0.05). (4) The adjusted R² value is 0.489, meaning that 48.9% of employee commitment is explained by compensation and job satisfaction, while the remaining 51.1% is influenced by other factors not included in this study. (5) The dominant variable affecting employee commitment is job satisfaction with a regression coefficient of 0.434.